Development and Optimization of Control Programs for 2.5-Coordinate Milling of Three-Dimensional Workpieces on CNC Machines - Averchenkov Andrey (EDP Sciences, 2021)
The paper presents new methods for optimizing milling operations on CNC machines when programming in CAM-systems, in particular, a method for improving the efficiency of processing three-dimensional workpieces by 2.5-coordinate milling on CNC machines for contour machining and a method for improving the productivity of contour milling of products with a variable allowance at a constant optimal value of the chip thickness, with the provision of geometric parameters of surface quality. Mathematical dependences of the surface quality parameters on the milling conditions are determined. Algorithms of automated analysis are presented, and methods for designing such operations are developed.